Comparison of total prevalence, perinatal prevalence, and livebirth prevalence of birth defects in Hunan Province, China, 2016–2020 - Zhou, Xu; Zeng, Xiu; Fang, Junqun; He, Jian; Kuang, Haiyan; Hua, Xinjun; Wang, Aihua (Frontiers in Public Health, 2024)
Birth defect of any type is undesirable and often pose a negetive impact on the health and development of the newborn. Birth defects surveillance with datasets from surveillance health-related programs are useful to predict the pattern of birth defects and take preventive measures. In this study, the total prevalence, perinatal prevalence, and livebirth prevalence of birth defects were compared.Data were obtained from the Birth Defects Surveillance System in Hunan Province, China, 2016-2020. The total prevalence is the number of birth defects (including livebirths, stillbirths, and selective terminations of pregnancy) per 1000 births (including livebirths and stillbirths). The perinatal prevalence is the number of birth defects (between 28 weeks gestation and 7 days postpartum) per 1000 births. The livebirth prevalence is the number of liveborn birth defects per 1000 births. (unit: ‰).Underestimated proportion (unit: %) is the reduction level of perinatal prevalence or livebirth prevalence compared to the total prevalence. Prevalence with 95% confidence intervals (CI) was calculated using the log-binomial method. Chi-square tests (χ2) were used to examine if significant differences existed in prevalence or underestimated proportion between different groups.A total of 847755 births were included in this study, and 23420 birth defects were identified, including 14459 (61.74%) birth defects with gestational age >=28 weeks, and 11465 (48.95%) birth defects in livebirths. The total prevalence, perinatal